Menumbuhkan Sikap Nasionalisme Warga Negara Muda di Era Globalisasi melalui Pendidikan Kewarganegaraan di Perguruan Tinggi (Studi pada Mahasiswa PGSD UAD) - Retnasari, Lisa; Hidayah, Yayuk (Universitas Pahlawan Tuanku Tambusai, 2020)
This study aims to determine the strategic role of Citizenship Education in fostering the attitude of nationalism of young citizens in the era of globalization. The research method used is a survey. The results showed. Citizenship Education in higher education can contribute to fostering nationalism with the values of Pancasila has a significant roleÂ for young citizen. Citizenship education learning approaches are more interactive through the problem-based learning model. In the learning process with the PBL model so that the maximum educator must have broad insight competencies.